Studi Self-efficacy Siswa Sekolah Berbasis Pesantren pada Mata Pelajaran IPA Kaitannya dengan Gender - Lailatul Fitria; Maria Chandra Sutarja; Badrud Tamam (UNIB Press, 2022)
Self-efficacy is one of student’s success predictors, so it should be one of the variables to be considered in learning activities. Research on self-efficacy in pesantren (Islamic boarding school) has not been widely disclosed. Therefore, it is necessary to conduct research related to gender-based self-efficacy in pesantren. The study used an ex-post-facto non-experimental quantitative design at one of the pesantren-based SMP and MTs in Pamekasan. There are 29 males and 39 females as the participants of this study. SOSESC-P was used as research instrument. Data were analyzed using t-test. Based on the result, there is no significant difference between the self-efficacy of male and female students in pesantren, with average score of 64.12 and 64.86 respectively. This indicates that the science learning process in pesantren has succeeded in bridging the achievement of self-efficacy of male and female students, with their comprehensive learning concept in 3 dimensions, namely (1) the deep dimension of religious morality, (2) the dimensions of science and technology, and (3) dimensions of skills needed in the 21st century. The result of this study can be used as evidence in policy-making, related to science learning and self-efficacy based on gender.